HPLC METHOD FOR DETERMINATION OF ACTIVE INGREDIENTS IN PESTICIDE FORMULATION SWITCH 62,5 WG - Velkoska-Markovska, Lenche; Davitkova, Jovana; Jankulovska, Mirjana S. (University Ss. Cyril and Methodius in Skopje, 2021)
Analytical quality control for pesticides achieved using appropriate methods is essential in providing their safe and adequate use in agriculture. This study presents a precise, fast, and a simple analytical method for determining active ingredients cyprodinil and fludioxonil in a fungicide formulation Switch 62,5 WG using high-performance liquid chromatography (HPLC). The development of the HPLC method was performed on a ZORBAX Eclipse Plus C18 (50 x 4.6 mm, 1.8 µm) analytical column using isocratic elution with a mobile phase consisting of acetonitrile and water in volume ratio 70:30, a flow rate of 1 mL/min, a constant column temperature at 25 ºC and UV detection at 220 and 270 nm. The run time of analysis under these chromatographic conditions was about 1.5 min. The method was validated by testing specificity, linearity, precision, recovery, LOD, LOQ, and accuracy according to the CIPAC (Collaborative International Pesticides Analytical Council) and SANCO (Directorate General Health and Consumer Protection) guidelines, and all the tested parameters were found within acceptance criteria. The values for multiple correlation coefficient (R2 ≥ 0.99), relative standard deviation (RSD < 1 %), recoveries ranged from 98.95 - 102.26 %, revealed that the developed method has a good linearity, precision and accuracy. The proposed method is suitable for routine analysis of active ingredients cyprodinil and fludioxonil in the formulation Switch 62,5 WG.
Keywords: cyprodinil, fludioxonil, HPLC method, pesticides, fungicide formulation